Environmental and Industrial Corrosion Practical and Theoretical Aspects - Valdez Salas, Benjamin; Schorr, Michael (IntechOpen, 2012)
Nowadays, it is generally accepted that in the natural and industrial environments, corrosion and pollution are interrelated harmful processes since many water, air and soil pollutants accelerate corrosion, and corrosion products such as rust, oxides and salts, also pollute water bodies at ports, rivers, dams, canals and shipyards. Both are pernicious processes that impair the durability of the infrastructure assets, the industry efficiency and profitability and the quality of the environment. Therefore, it is essential to develop and to apply corrosion engineering control methods and techniques, in particular those being environment-friendly. In this crucial time of worldwide energy crisis and economic turmoil, cost effective corrosion control will extend the life of the infrastructure saving large expenses in materials, equipment and structures. This book will contribute to achieve this important mission!